System criminality in international law - Wilt, Harmen van der, 1955-; Nollkaemper, André; Dolman, M. M. (Menno M.); Kleffner, Jann K. (Cambridge books online., 2009)
How does international law respond to situations where collective entities order, encourage or allow the committing of international crimes?